Highly efficient 2 μm Tm:YAG ceramic laser - Gao, W. L. (2013)
We have experimentally demonstrated a highly efficient diode-pumped Tm:YAG ceramic laser operating at 2 μm wavelength. The maximum output power of 6.05 W was realized with a slope efficiency as high as 65%. As far as we know, it is the highest slope efficiency reported for Tm:YAG ceramic laser. The wavelength tuning experiment of Tm:YAG ceramic laser was carried out and the results suggest that Tm:YAG ceramic laser could operate simultaneously at multiple wavelengths in a wide range of 1884–2017 nm.